Dietary L-Methionine modulates the gut microbiota and improves the expression of tight junctions in an in vitro model of the chicken gastrointestinal tract - Min-Jin Kwak; Anna Kang; JuYoung Eor; Sangdon Ryu; Youbin Choi; Jung Min Heo; Minho Song; Jong Nam Kim; Hyeon-Jin Kim; Younghoon Kim (Animal Microbiome, 2024)
Abstract Background The poultry industry encounters a number of factors that affect growth performance and productivity; nutrition is essential for sustaining physiological status and protecting against stressors such as heat, density, and disease. The addition of vitamins, minerals, and amino acids to the diet can help restore productivity and support the body’s defense mechanisms against stress. Methionine (Met) is indispensable for poultry’s energy metabolism, physiology, performance, and feed utilization capacity. Through this study, we aimed to examine the physiological effects of methionine supplementation on poultry as well as alterations of intestinal microbiome. Methods We utilized the DL- and L- form of methionine on Caenorhabditis elegans and the FIMM (Fermentor for intestine microbiota model) in-vitro digesting system. A genomic-analysis of the transcriptome confirmed that methionine supplementation can modulate growth-related physiological metabolic pathways and immune responses in the host poultry. The C. elegans model was used to assess the general health benefits of a methionine supplement for the host. Results Regardless of the type or concentration of methionine, supplementation with methionine significantly increased the lifespan of C. elegans. Feed grade L-Methionine 95%, exhibited the highest lifespan performance in C. elegans. Methionine supplementation increased the expression of tight junction genes in the primary intestinal cells of both broiler and laying hens, which is directly related to immunity. Feed grade L-Methionine 95% performed similarly or even better than DL-Methionine or L-Methionine treatments with upper doses in terms of enhancing intestinal integrity. In vitro microbial cultures of healthy broilers and laying hens fed methionine revealed changes in intestinal microflora, including increased Clostridium, Bacteroides, and Oscillospira compositions. When laying hens were given feed grade L-Methionine 95% and 100%, pathogenic Campylobacter at the genus level was decreased, while commensal bacteria were increased. Conclusions Supplementation of feed grade L-Methionine, particularly L-Methionine 95%, was more beneficial to the host poultry than supplementing other source of methionine for maintaining intestinal integrity and healthy microbiome.